Formation behavior of bubbles and its effect on joining strength in dissimilar materials laser spot joining between PET and SUS304 - Yukio MIYASHITA (The Japan Society of Mechanical Engineers, 2015)
Formation behavior of bubbles and its effect on strength in PET/SUS304 dissimilar materials laser spot lap joint was studied. Surface of SUS304 was irradiated through transparent PET with fiber laser. Static and cyclic contact force was applied at the welding region during the joining process. Strength of the joint was evaluated by conducting tensile shear test. The formation behavior of bubbles inside PET nearby the interface changed with change in condition of contact force. In case of applying lower static contact force, welded area and failure load of the joint increased with increase in contact force. This result might be due to flow of molten PET by applying compressive force. On the other hand, when higher static contact force was applied, welded area and failure load of the joint decreased, because suppress of the flowing for molten and softened PET occurred. The joint joined with applying cyclic contact force showed lower values of welded area and failure load compared to the joint joined with applying the same maximum static contact force. According to fracture surface observation, crack mainly passed through bubbles to failure in all joints. Apparent strength was calculated by failure load and welded area obtained. The strength of the joint decreased with increase in bubbles density, except the joint joined without contact force. In case of joint joined without contact force, large bubbles were formed and decreased strength. Bubble size formed was small when contact force was applied. Density of bubbles affected strength of the joint and changed by applying contact force, particularly that decreased by applying cyclic contact force. It is considered that applying the contact force is an effective way to control formation behavior of bubbles and results in improvement for reliability of the dissimilar material joint between plastic and metallic materials.